Performance of tomato M7 mutant lines and their similarities to the parents based on SSR markers (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Arrufitasari PN, Sutjahjo SH, Wirnas D. 2022. Performance of tomato M7 mutant lines and their similarities to the parents based on SSR markers. Biodiversitas 23: 1239-1245. Tomato cultivation in the lowlands can be an alternative to increase tomato production so that high-yielding and lowland adaptive varieties are required. This study was aiming at determining the performance of  M7 mutant lines and their similarities to the parents based on SSR markers. The experiments were conducted at KP Leuwikopo (250 m asl) and Plant Molecular Biology Laboratory, IPB University, Indonesia. The results showed that the G4 line had the highest productivity among the tested genotypes (36.72 ton ha-1) and significantly differed from all check varieties. The highest number of fruit per plant was 51.67 in the G7 line. On the other hand, G2, G3, G7, G8, and G10 lines had the lowest percentage weight and the number of fruits cracking and were not significantly different from the check varieties (Tora and Mawar). A total of 7 SSR primers detected 87 alleles with a range of 7-15 alleles per locus. The similarity between mutant lines and their parents ranged from 44-69%. The mutant most closely resembled the parent was the G3 line, while the most different based on molecular markers was the G9 line.